Fingolimod Treatment in Relapsing-Remitting Multiple Sclerosis Patients: A Prospective Observational Multicenter Postmarketing Study. (22nd July 2015) - Totaro, Rocco; Di Carmine, Caterina; Costantino, Gianfranco; Fantozzi, Roberta; Bellantonio, Paolo; Fuiani, Aurora; Mundi, Ciro; Ruggieri, Stefano; Marini, Carmine; Carolei, Antonio
Abstract : Objective . The aim of this prospective observational multicenter postmarketing study was to evaluate fingolimod efficacy in a real world clinical setting. Methods . One hundred forty-two subjects with relapsing-remitting multiple sclerosis (RRMS) were enrolled in three multiple sclerosis centers throughout Central and Southern Italy between January 2011 and September 2013. After enrollment, regular visits and EDSS assessment were scheduled every 3 months, and MRI scan was obtained every 12 months. Patients were followed up from 1 to 33 months (mean 14.95 ± 9.15 months). The main efficacy endpoints included the proportion of patients free from clinical relapses, from disability progression, from magnetic resonance imaging activity, and from any disease activity. Results . Out of 142 patients enrolled in the study, 88.1% were free from clinical relapse and 69.0% were free from disability progression; 68.5% of patients remained free from new or newly enlarging T2 lesions and 81.7% of patients were free from gadolinium enhancing lesions. Overall the proportion of patients free from any disease activity was 41.9%. Conclusions . Our data in a real world cohort are consistent with previous findings that yield convincing evidence for the efficacy of fingolimod in patients with RRMS.